PREVALENCE OF OVERWEIGHT AND OBESITY IN SCHOOL: SYSTEMATIC LITERATURE REVIEW (Fiep Bulletin - online, 2015)
The obesity is one of the health problems most graves and increasing that affect the world. Nowadays, it is considered a problem of public health, especially for the fact of increase of its prevalence children and teenagers. In Brazil, it is noticeable worried data in all regions, fundamentally among schools. The causes of obesity are multifactorial,  being the majority of it are the physical inactivity and inadequate alimentation, rich in fat. The objective of this study was to analyze the prevalence of the overweight and obesity in schools to create strategies of prevention to this sickness. It was a research using literature revision with schools from 6 to 10 years that had as base of data articles and periodic published electronically in the databases: Scielo, Pubmed, Lilacs and Bibblioteca Virtual em Saude in the period between January of 2002 and January of 2013. Studies point out that because of the technology advance and nutritional transition in Brazil , children have been turned more vulnerable to the risk of obesity, since risks in fat, sugars and a few physical activity. Also, the study showed a bigger prevalence of overweight and obesity in boys and in private schools. With the achievement of this results, this evidences the importance of implant educational programs, with the especial goal of formation of a nutritional behaviours healthier and the regular practice of physical ativities, since childhood.
Keywords: Overweight; Obesity; School; Prevalence.